A kind of radiation cooling coating with anti-fouling property and preparation method thereof

Through the synergy between modified hollow porous carbon microspheres and TiO2 and NiAl2O4, the problem of insufficient pollution resistance of radiation refrigeration coatings in outdoor environments is solved, and the efficient refrigeration and pollution resistance is achieved. It is suitable for energy, aerospace and Construction field.

CN118994983BActive Publication Date: 2024-12-20HUNAN TONGQIU RADIUM SHIELD TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411489124.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-20
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Existing radiation refrigeration coatings are susceptible to contamination in outdoor environments, resulting in a degradation of refrigeration performance. How to improve stain resistance while maintaining high infrared emissivity has become a challenge.

Method used

Modified hollow porous carbon microspheres are used as fillers to form a core-shell structure through grafting reaction of silane coupling agent and polymer, and combined with TiO2 and NiAl2O4, the hydrophobicity and refrigeration properties of the coating are enhanced.

Benefits of technology

It achieves a high emissivity in the infrared band, and significantly improves the stain resistance and refrigeration performance of the coating, ensures long-term and efficient refrigeration effect, and is simple in preparation process, low in cost, environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention belongs to the technical field of refrigeration coatings, and specifically relates to a radiation refrigeration coating with stain resistance and a preparation method thereof. The radiation refrigeration coating with stain resistance comprises the following raw materials in parts by weight: 40-60 parts of acrylic resin, TiO 2 13‑20 parts, NiAl2O 4 23-40 parts, filler 8-15 parts, thickener 0.5-1.3 parts, defoamer 0.3-0.8 parts, film-forming aid 0.5-1.5 parts, cross-linking agent 1-5 parts, dispersant 0.5-1.3 parts, water 60-80 parts. The coating of the present invention not only has an efficient radiation cooling effect; at the same time, its surface also has super hydrophobicity and stain resistance, can effectively resist the invasion of pollutants such as dust and rain in the outdoor environment, and has good application prospects in the fields of energy, aerospace, and construction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refrigeration coatings, and in particular relates to a radiation refrigeration coating with pollution resistance and a preparation method thereof. Background Art

[0002] With the intensification of the global energy crisis and the improvement of environmental awareness, the search for efficient and energy-saving refrigeration technology has become an important direction for scientific research and industrial application. Radiative cooling technology, as a passive cooling method that does not require electric drive, has received widespread attention in recent years due to its characteristics of no energy consumption, environmental friendliness and wide application. This technology uses the high emissivity characteristics of specific materials in the infrared band to dissipate heat into the universe in the form of radiation, thereby achieving the purpose of cooling. However, although radiative cooling technology shows great potential in theory, in practical applications, especially in the face of complex and changeable outdoor environments, the stain resistance of its key material, radiative cooling coatings, has become a major technical bottleneck restricting its widespread application. Specifically, existing radiative cooling materials, such as rare earth oxides and semiconductor materials, have excellent performance in infrared emissivity and can effectively radiate heat into the universe, but under long-term outdoor exposure, these materials are extremely susceptible to a variety of pollutants such as dust, rain, and oil. Pollutants not only cover the surface of the material, reducing the efficiency of infrared radiation, but may also damage the internal structure of the material through penetration, resulting in a significant decrease in refrigeration performance.

[0003] In order to improve the stain resistance of coatings, researchers have conducted a lot of exploration and developed a variety of stain-resistant coatings. These coatings usually introduce super-hydrophobic surfaces and self-cleaning functional materials (such as TiO2 photocatalytic materials) to make the coating surface have the ability to repel pollutants such as water and oil. Super-hydrophobic surfaces reduce surface energy, making water droplets form spheres when they contact the coating surface, making it easy to roll off, thereby preventing water penetration and dirt adhesion. Self-cleaning functional materials can decompose organic pollutants under light conditions to achieve self-cleaning of the coating.

[0004] Although the above technologies have made great progress in improving the stain resistance of coatings, they still face many technical bottlenecks and challenges when integrated with radiant cooling technology. How to ensure that the high emissivity characteristics of radiant cooling coatings in the infrared band are not sacrificed while improving the stain resistance has become the focus and difficulty of current research. Therefore, the development of a radiant cooling coating that can both efficiently cool and have good stain resistance has become the key to promoting technological progress in this field. Summary of the invention

[0005] The first purpose of the present invention is to provide a radiation cooling coating with pollution resistance. The coating of the present invention has the advantages of radiation cooling, water resistance and pollution resistance. It uses specially modified hollow porous carbon microspheres as fillers, which not only retains good infrared emission performance, but also gives the coating excellent pollution resistance. It conforms to the concept of sustainable development and has broad application prospects and market potential.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A radiant cooling coating with stain resistance comprises the following raw materials in parts by weight: 40-60 parts of acrylic resin, 13-20 parts of TiO2, 23-40 parts of NiAl2O4, 8-15 parts of filler, 0.5-1.3 parts of thickener, 0.3-0.8 parts of defoamer, 0.5-1.5 parts of film-forming aid, 1-3 parts of cross-linking agent, 0.5-1.3 parts of dispersant, and 60-80 parts of water; the filler is modified hollow porous carbon microspheres, and the preparation process is as follows:

[0008] (1) adding hollow porous carbon microspheres and a silane coupling agent into a solvent to react to obtain hollow porous carbon microspheres modified with a silane coupling agent;

[0009] (2) The hollow porous carbon microspheres modified with a silane coupling agent prepared in step (1), N-dodecyl acrylamide, N-vinyl-2-pyrrolidone, a surfactant, and an initiator are added to a solvent for reaction to obtain modified hollow porous carbon microspheres.

[0010] In step (1), the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the solvent is ethanol; the mass ratio of the hollow porous carbon microspheres to the volume of the silane coupling agent is 1 g: 1-3 mL; the average particle size of the hollow porous carbon microspheres is 100-300 nm;

[0011] In step (2), the surfactant is sodium dodecyl sulfate, the initiator is azobisisobutyronitrile, and the solvent is water;

[0012] The mass ratio of the hollow porous carbon microspheres modified by the silane coupling agent to N-dodecyl acrylamide, N-vinyl-2-pyrrolidone, surfactant and initiator is 1:(7-12):(1-4):(0.1-0.5):(0.03-0.08);

[0013] The thickener is a polyurethane thickener; the defoamer is polydimethylsiloxane; the film-forming aid is alcohol ester dodeca or dipropylene glycol butyl ether; the crosslinking agent is a blocked isocyanate crosslinking agent; and the dispersant is gul gum.

[0014] The silane coupling agent reacts with the hydroxyl and other functional groups on the surface of the carbon microspheres through its trimethoxysilane part, and the silane coupling agent is grafted to the surface of the carbon microspheres, forming a layer of low surface energy organic silicon layer on the surface of the microspheres. The two monomers N-dodecyl acrylamide and N-vinyl-2-pyrrolidone undergo polymerization under the action of the initiator, and further form a rough, low surface energy polymer layer on the surface of the carbon microspheres to obtain modified hollow porous carbon microspheres with a core-shell structure. The combined effect of low surface energy and rough structure makes the modified hollow porous carbon microspheres have a strong repulsion to water, that is, they show hydrophobicity.

[0015] Furthermore, the thickener is COAPUR XS 71; and the solid content of the blocked isocyanate crosslinking agent is 75±2%.

[0016] Furthermore, the reaction temperature of step (1) is 50-60°C, and the reaction time is 7-9h; the reaction temperature of step (2) is 60-70°C, and the reaction time is 8-12h.

[0017] Furthermore, the average particle size of TiO2 is 0.4µm.

[0018] Furthermore, the NiAl2O4 is prepared by the following method:

[0019] NiO and Al2O3 are mixed, ball-milled, and then a polyvinyl alcohol aqueous solution is added and mixed evenly to obtain a mixture, the mixture is pressed into a shape, and calcined at 900-1200°C for 2-3h to obtain the mixture.

[0020] Furthermore, the molar ratio of NiO to Al2O3 is 1:(1-2), the concentration of the polyvinyl alcohol aqueous solution is 4wt%, wherein the amount of polyvinyl alcohol is 1.2-1.6wt% of the total mass of NiO and Al2O3.

[0021] The second object of the present invention is to provide a method for preparing a radiation cooling coating with pollution resistance, which has simple preparation process, low cost, and is environmentally friendly and pollution-free.

[0022] In order to achieve the above object, the technical solution adopted by the present invention is:

[0023] A method for preparing a radiation cooling coating with anti-fouling properties comprises the following steps:

[0024] Weigh acrylic resin, TiO2, NiAl2O4, filler, thickener, defoamer, film-forming aid, crosslinking agent and dispersant according to the above weight parts, then add each component into water and stir to mix evenly to obtain the product.

[0025] The beneficial technical effects of the present invention are:

[0026] 1. The TiO2 and NiAl2O4 in the radiant cooling coating provided by the present invention can work synergistically to provide excellent cooling performance. The experimental results show that the radiant cooling coating in the present invention significantly enhances the emissivity of the coating at a wavelength of 8-13µm, thereby reducing the surface temperature and achieving an efficient passive cooling effect. At the same time, within 250-2500nm, the coating maintains a good reflectance, reduces the absorption of solar radiation heat, and further enhances its cooling capacity.

[0027] 2. The filler in the radiant cooling coating provided by the present invention is a modified hollow porous carbon microsphere, which is obtained by grafting and copolymerizing the hollow porous carbon microsphere with a silane coupling agent, N-dodecyl acrylamide, and N-vinyl-2-pyrrolidone to form a layer of polymer on the surface of the carbon microsphere, thereby obtaining a modified hollow porous carbon microsphere with a core-shell structure. This design not only retains the original porosity of the carbon microsphere, but also gives the coating hydrophobicity, so that the contact angle between the coating and water can reach about 135°, which can reduce the adhesion between the coating and moisture, dust and oil, significantly reduce the impact of the external environment on the performance of the coating, and ensure that the coating maintains efficient refrigeration performance for a long time. DETAILED DESCRIPTION

[0028] The following is a further detailed description of the present invention in conjunction with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those of ordinary skill in the technical field to which the present invention belongs, without departing from the concept of the present invention, several simple deductions or replacements can also be made, all of which should be deemed to belong to the protection scope of the present invention. The specific conditions not indicated in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0029] The TiO2 involved in the invention has an average particle size of 0.4µm; a hollow porous carbon microsphere particle size of 200-300nm; a water-based acrylic resin with a solid content of 47-49%, a viscosity of 1500-5000mPa·s / 25°C, and a pH value of 7.0-8.0; and a blocked isocyanate solid content of 75±2%.

[0030] Example 1

[0031] A radiant cooling coating with stain resistance comprises the following raw materials in parts by weight: 50 parts of waterborne acrylic resin, 16 parts of TiO2, 32 parts of NiAl2O4, 11 parts of modified hollow porous carbon microspheres, 1 part of COAPUR XS 71, 0.5 parts of polydimethylsiloxane, 1 part of alcohol ester dodecahydrate, 3 parts of blocked isocyanate, 0.9 parts of Gul gum and 70 parts of water.

[0032] The preparation process of the modified hollow porous carbon microspheres is as follows:

[0033] (1) Add 1 g of hollow porous carbon microspheres to 10 mL of ethanol and stir to mix evenly. Then add 2 mL of γ-methacryloxypropyltrimethoxysilane to 30 mL of ethanol and stir to mix evenly. Then mix the two solutions, ultrasonically treat for 60 min, and react at 55 °C for 8 h. After the reaction is completed, filter, wash the filtered product repeatedly with ethanol, and then vacuum dry to obtain hollow porous carbon microspheres modified with silane coupling agent.

[0034] (2) Dissolve 0.25 g of sodium dodecyl sulfate in 50 mL of water, then add 1 g of the hollow porous carbon microspheres modified by the silane coupling agent prepared in step (1), 10 g of N-dodecyl acrylamide, and 3 g of N-vinyl-2-pyrrolidone into the water, stir and mix at 300 rpm for 30 min under a nitrogen atmosphere, add 0.05 g of azobisisobutyronitrile at 65° C. and react for 10 h; after the reaction is completed, filter the reaction solution, collect the precipitate, wash it repeatedly with ethanol, and then vacuum dry it to obtain the product.

[0035] The above NiAl2O4 is prepared by the following method:

[0036] NiO powder and Al2O3 powder are mixed in a molar ratio of 1:1.5, and ball-milled with anhydrous ethanol as a medium to make the two powders mix evenly, and then the ball-milled powder is dried; polyvinyl alcohol aqueous solution (4wt%) is added to the dried powder and mixed evenly to obtain a mixture, wherein the amount of polyvinyl alcohol is 1.4wt% of the total mass of the NiO powder and the Al2O3 powder, the hydraulic press pressure is adjusted to 18MPa, the pressure is maintained for 20s, the above mixture is pressed into shape, and then calcined at 1000℃ for 2.5h to obtain the mixture.

[0037] This embodiment also provides a method for preparing a radiation cooling coating with anti-fouling properties, comprising the following steps:

[0038] According to the above weight parts, water-based acrylic resin, TiO2, NiAl2O4, modified hollow porous carbon microspheres, COAPUR XS 71, polydimethylsiloxane, alcohol ester dodecahydrate, blocked isocyanate, and guar gum were weighed, and then the components were added into water and stirred at 800 rpm for 60 min to obtain the product.

[0039] Example 2

[0040] A radiant cooling coating with stain resistance comprises the following raw materials in parts by weight: 40 parts of water-based acrylic resin, 13 parts of TiO2, 23 parts of NiAl2O4, 8 parts of modified hollow porous carbon microspheres, 0.5 parts of COAPUR XS 71, 0.3 parts of polydimethylsiloxane, 0.5 parts of dipropylene glycol butyl ether, 1 part of blocked isocyanate, 0.5 parts of Gul gum, and 60 parts of water.

[0041] The preparation process of the modified hollow porous carbon microspheres is as follows:

[0042] (1) Add 1 g of hollow porous carbon microspheres to 10 mL of ethanol and stir to mix evenly. Then add 1 mL of γ-methacryloxypropyltrimethoxysilane to 30 mL of ethanol and stir to mix evenly. Then mix the two solutions, treat with ultrasound for 60 min, and react at 50 °C for 9 h. After the reaction is completed, filter, wash the filtered product repeatedly with ethanol, and then vacuum dry to obtain hollow porous carbon microspheres modified with silane coupling agent.

[0043] (2) Dissolve 0.1 g of sodium dodecyl sulfate in 50 mL of water, then add 1 g of the hollow porous carbon microspheres modified by the silane coupling agent prepared in step (1), 7 g of N-dodecyl acrylamide, and 1 g of N-vinyl-2-pyrrolidone into the water, stir and mix at 300 rpm for 30 min under a nitrogen atmosphere, add 0.03 g of azobisisobutyronitrile at 60° C. and react for 12 h; after the reaction is completed, filter the reaction solution, collect the precipitate, wash it repeatedly with ethanol, and then vacuum dry it to obtain the product.

[0044] The above NiAl2O4 is prepared by the following method:

[0045] NiO powder and Al2O3 powder are mixed in a molar ratio of 1:1, and ball-milled with anhydrous ethanol as a medium to make the two powders mixed evenly, and then the ball-milled powder is dried; polyvinyl alcohol aqueous solution (4wt%) is added to the dried powder and mixed evenly to obtain a mixture, wherein the amount of polyvinyl alcohol is 1.4wt% of the total mass of the NiO powder and the Al2O3 powder; the hydraulic press pressure is adjusted to 18MPa, the pressure is maintained for 20s, the above mixture is pressed into shape, and then calcined at 900℃ for 3h to obtain the mixture.

[0046] This embodiment also provides a method for preparing a radiation cooling coating with anti-fouling properties, comprising the following steps:

[0047] The aqueous acrylic resin, TiO2, NiAl2O4, modified hollow porous carbon microspheres, COAPUR XS 71, polydimethylsiloxane, dipropylene glycol butyl ether, blocked isocyanate crosslinking agent, and gul gum were weighed according to the above weight parts, and then the components were added into water and stirred at 800 rpm for 60 min to obtain the product.

[0048] Example 3

[0049] A radiant cooling coating with stain resistance comprises the following raw materials in parts by weight: 60 parts of waterborne acrylic resin, 20 parts of TiO2, 40 parts of NiAl2O4, 15 parts of modified hollow porous carbon microspheres, 1.3 parts of COAPUR XS 71, 0.8 parts of polydimethylsiloxane, 1.5 parts of alcohol ester dodecahydrate, 3 parts of blocked isocyanate crosslinking agent, 1.3 parts of Gul gum and 80 parts of water.

[0050] The preparation process of the modified hollow porous carbon microspheres is as follows:

[0051] (1) Add 1 g of hollow porous carbon microspheres to 10 mL of ethanol and stir to mix evenly. Then add 3 mL of γ-methacryloxypropyltrimethoxysilane to 30 mL of ethanol and stir to mix evenly. Then mix the two solutions, treat with ultrasound for 60 min, and react at 60 ° C for 7 h. After the reaction is completed, filter, wash the filtered product repeatedly with ethanol, and then vacuum dry to obtain hollow porous carbon microspheres modified with silane coupling agent.

[0052] (2) Dissolve 0.5 g of sodium dodecyl sulfate in 50 mL of water, then add 1 g of the hollow porous carbon microspheres modified by the silane coupling agent prepared in step (1), 12 g of N-dodecyl acrylamide, and 4 g of N-vinyl-2-pyrrolidone into the water, stir and mix at 300 rpm for 30 min under a nitrogen atmosphere, add 0.08 g of azobisisobutyronitrile at 70° C. and react for 8 h; after the reaction is completed, filter the reaction solution, collect the precipitate, wash it repeatedly with ethanol, and then vacuum dry it to obtain the product.

[0053] The above NiAl2O4 is prepared by the following method:

[0054] NiO powder and Al2O3 powder are mixed in a molar ratio of 1:2, and ball-milled with anhydrous ethanol as a medium to make the two powders mix evenly, and then the ball-milled powder is dried; polyvinyl alcohol aqueous solution (4wt%) is added to the dried powder and mixed evenly to obtain a mixture, wherein the amount of polyvinyl alcohol is 1.6wt% of the total mass of the NiO powder and the Al2O3 powder, the hydraulic press pressure is adjusted to 18MPa, the pressure is maintained for 20s, the above mixture is pressed into shape, and then calcined at 1100℃ for 2h.

[0055] This embodiment also provides a method for preparing a radiation cooling coating with anti-fouling properties, comprising the following steps:

[0056] According to the above weight parts, water-based acrylic resin, TiO2, NiAl2O4, modified hollow porous carbon microspheres, COAPUR XS 71, polydimethylsiloxane, alcohol ester dodecahydrate, blocked isocyanate, and guar gum were weighed, and then the components were added into water and stirred at 800 rpm for 60 min to obtain the product.

[0057] Comparative Example 1

[0058] The difference between Comparative Example 1 and Example 1 is that the radiation cooling coating with anti-fouling properties omits NiAl2O4.

[0059] Comparative Example 2

[0060] The difference between Comparative Example 2 and Example 1 is that the anti-fouling radiation cooling coating omits NiAl2O4, and the amount of TiO2 is adjusted to the sum of the amounts of TiO2 and NiAl2O4.

[0061] Comparative Example 3

[0062] The difference between Comparative Example 3 and Example 1 is that the modified hollow porous carbon microspheres are replaced with hollow porous carbon microspheres in the radiant cooling coating with anti-fouling properties.

[0063] Comparative Example 4

[0064] The difference between this comparative example 4 and example 1 is that the preparation process of the filler is as follows:

[0065] Dissolve 0.25g of sodium dodecyl sulfate in 50mL of water, then add 10g of N-dodecyl acrylamide and 3g of N-vinyl-2-pyrrolidone into the water, stir and mix at 300rpm for 30min under a nitrogen atmosphere, add 0.05g of azobisisobutyronitrile at 65°C and react for 10h; after the reaction is completed, filter the reaction solution, collect the precipitate and wash it repeatedly with ethanol, and then vacuum dry to obtain the product. Then mix the product with 1g of hollow porous carbon microspheres to obtain the product.

[0066] Comparative Example 5

[0067] The difference between this comparative example 5 and example 1 is that the preparation process of the filler is as follows:

[0068] (1) Add 1 g of hollow porous carbon microspheres to 10 mL of ethanol and stir to mix evenly. Then add 2 mL of γ-methacryloxypropyltrimethoxysilane to 30 mL of ethanol and stir to mix evenly. Then mix the two solutions, ultrasonically treat for 60 min, and react at 55 °C for 8 h. After the reaction is completed, filter, wash the filtered product repeatedly with ethanol, and then vacuum dry to obtain hollow porous carbon microspheres modified with silane coupling agent.

[0069] (2) Dissolve 0.25 g of sodium dodecyl sulfate in 50 mL of water, then add 1 g of the hollow porous carbon microspheres modified with a silane coupling agent prepared in step (1) and 13 g of N-vinyl-2-pyrrolidone into the water, stir and mix at 300 rpm for 30 min under a nitrogen atmosphere, add 0.05 g of azobisisobutyronitrile at 65 °C and react for 10 h; after the reaction is completed, filter the reaction solution, collect the precipitate, wash it repeatedly with ethanol, and then vacuum dry it to obtain the product.

[0070] Test Example 1

[0071] The adhesion of the coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 was tested according to the standard of GB9286-1998, and the specific steps were as follows: The coatings obtained in Examples 1 to 3 and Comparative Examples 1 to 5 of the present invention were respectively coated on a metal substrate having a size of 150 mm×70 mm×4 mm. A single-edged tool was then used to perform grid-like cutting on the surface of the sample (3 cuts in each direction, 3 mm apart, to form a 4-grid grid). The adhesion of the coating was evaluated by a tape peeling test, and the adhesion was divided into 0 to 5 levels according to the peeling condition, where:

[0072] Grade 0 represents the best adhesion, with no coating shedding and completely smooth cut edges;

[0073] Level 1 means that there are small pieces of paint peeling off at the intersection of the cuts, and the actual damage in the cross-cut area is less than or equal to 5%;

[0074] Level 2 means that the peeling area of ​​the edge of the cut and intersection is greater than 5% and less than 15%;

[0075] Level 3 means that there is partial peeling or large-area paint peeling along the edge of the cut, and some grid parts are even peeled off in one piece, with the peeling area exceeding 15% and not exceeding 35%;

[0076] Level 4 means that some squares are partially or completely peeled off, and the peeling area is greater than 35% and less than 65%;

[0077] Level 5 means that the paint peeling area is greater than 65% and the adhesion is the worst.

[0078] The results are shown in Table 1.

[0079] Table 1

[0080]

[0081] From the experimental results in Table 1, it can be seen that the adhesion of the coatings described in Examples 1 to 3 can meet the use requirements. In Comparative Examples 1 to 2, the dosage of TiO2 and NiAl2O4 was adjusted, so that the adhesion of the coatings decreased, and the grades were all grade 1. In Comparative Examples 3-5, the preparation process of the hollow porous carbon microspheres was adjusted or replaced, and the adhesion of the coatings also decreased. This may be because the porous structure and surface properties of the modified hollow porous carbon microspheres affect their compatibility and binding ability with the resin, thereby affecting the adhesion of the coating.

[0082] Test Example 2

[0083] The radiative cooling coatings prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were coated on a metal substrate material to obtain a coating with a thickness of 200 µm. According to the standard requirements of GB / T 25261-2018 "Reflective Insulation Coatings for Buildings", the reflectance of the samples in the wavelength range of 250-2500 nm and the emissivity in the atmospheric window band of 8-13 μm were tested. The results are shown in Table 2.

[0084] Table 2

[0085]

[0086] Solar reflectance is an important indicator to measure the ability of a coating or material surface to reflect sunlight. A high solar reflectance indicates that the coating can effectively reflect sunlight, reduce the absorption of solar radiation energy, and thus reduce the surface temperature, achieving energy saving and cooling effects. Surface materials with higher atmospheric window emissivity have better cooling effects.

[0087] From the experimental results in Table 2, it can be seen that the coatings described in Examples 1 to 3 of the present invention all have high solar reflectance and atmospheric window emissivity. Compared with Example 1, the solar reflectance and atmospheric window emissivity of Comparative Example 1 are significantly reduced. It can be seen that NiAl2O4 plays a key role in improving the solar reflectance and atmospheric window emissivity in the radiation cooling coating. The results of Examples 1-3 and Comparative Examples 1-2 show that TiO2 and NiAl2O4 can work synergistically to improve the cooling performance of the radiation material.

[0088] Test Example 3

[0089] (1) The coatings obtained in Examples 1 to 3 and Comparative Examples 3 to 5 were coated on a metal substrate to ensure that the coating surface was flat, smooth and wrinkle-free. 1 μl of distilled water was dripped on the coating surface. The static contact angle of each group of coatings was tested using a surface tension contact angle meter. Three different positions were taken for each group. The results are shown in Table 3.

[0090] (2) According to the standard of GB / T 9755-2014, the stain resistance of the coatings obtained in Examples 1 to 3 of the present invention and Comparative Examples 3 to 5 was tested. The results are shown in Table 3.

[0091] (3) Use an oil-based pen to write the word "good" on the surface of the above coating. After waiting for 5 minutes, wipe it with a clean rag. Observe and record the surface condition of the coating after wiping, such as whether the writing is completely removed and whether the coating is damaged. Repeat this cycle several times to evaluate the number of times the coating can withstand scrubbing. The results are shown in Table 3.

[0092] Table 3

[0093]

[0094] It can be seen from the experimental results in Table 3 that the water contact angles of the radiant cooling coatings of Examples 1 to 3 of the present invention are all greater than those of Comparative Examples 3 to 5, wherein the water contact angle of Example 1 can reach 135.8°. Comparative Examples 3 to 5 adjusted the preparation method of the filler, so that the overall hydrophobic effect is not ideal. This shows that the addition of the modified hollow porous carbon microspheres prepared in Examples 1 to 3 to the coating greatly improves the hydrophobicity of the coatings in Examples 1 to 3.

[0095] The stain resistance of the coatings in Examples 1 to 3 is no more than 5%, and the coatings are scrub-resistant and can be completely wiped clean without leaving any traces, and have excellent scrub resistance. The above experimental results fully demonstrate that the coatings of the present invention have excellent water resistance and stain resistance.

[0096] In summary, the coating of the present invention can not only show excellent emission performance in the infrared band and achieve efficient radiation cooling effect; at the same time, its surface also has super hydrophobicity and stain resistance, and can effectively resist the invasion of pollutants such as dust, rain, oil and so on in the outdoor environment. In addition, the coating also has the advantages of simple preparation process, low cost, environmental protection and no pollution, and has good application prospects in the fields of energy, aerospace and construction.

[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. The basic principles and main features of the present invention have been described above with specific implementation schemes. On the basis of the present invention, some modifications or replacements may be made thereto, but these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of protection claimed by the present invention.

Claims

1. A radiant cooling coating with anti-fouling properties, characterized in that: The invention comprises the following raw materials in parts by weight: 40-60 parts of acrylic resin, 13-20 parts of TiO2, 23-40 parts of NiAl2O4, 8-15 parts of filler, 0.5-1.3 parts of thickener, 0.3-0.8 parts of defoamer, 0.5-1.5 parts of film-forming aid, 1-3 parts of crosslinking agent, 0.5-1.3 parts of dispersant and 60-80 parts of water; The filler is modified hollow porous carbon microspheres, and the preparation process is as follows: (1) adding hollow porous carbon microspheres and a silane coupling agent into a solvent for reaction to obtain hollow porous carbon microspheres modified with a silane coupling agent; (2) adding the hollow porous carbon microspheres modified with a silane coupling agent prepared in step (1), N-dodecyl acrylamide, N-vinyl-2-pyrrolidone, a surfactant, and an initiator to a solvent for reaction to obtain modified hollow porous carbon microspheres; In step (1), the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, and the solvent is ethanol; the mass ratio of the hollow porous carbon microspheres to the volume of the silane coupling agent is 1 g: 1-3 mL; the average particle size of the hollow porous carbon microspheres is 100-300 nm; In step (2), the surfactant is sodium dodecyl sulfate, the initiator is azobisisobutyronitrile, and the solvent is water; The mass ratio of the hollow porous carbon microspheres modified by the silane coupling agent to N-dodecyl acrylamide, N-vinyl-2-pyrrolidone, surfactant and initiator is 1:(7-12):(1-4):(0.1-0.5):(0.03-0.08); The thickener is a polyurethane thickener; the defoamer is polydimethylsiloxane; the film-forming aid is alcohol ester dodeca or dipropylene glycol butyl ether; the crosslinking agent is a blocked isocyanate crosslinking agent; and the dispersant is gul gum.

2. The radiant cooling coating with anti-fouling properties according to claim 1, characterized in that: The reaction temperature of step (1) is 50-60°C and the reaction time is 7-9h; the reaction temperature of step (2) is 60-70°C and the reaction time is 8-12h.

3. The radiant cooling coating with anti-fouling properties according to claim 1, characterized in that: The NiAl2O4 is prepared by the following method: NiO and Al2O3 are mixed, ball-milled, and then a polyvinyl alcohol aqueous solution is added and mixed evenly to obtain a mixture, the mixture is pressed into a shape, and calcined at 900-1200°C for 2-3h to obtain the mixture.

4. The radiant cooling coating with anti-fouling properties according to claim 3, characterized in that: The molar ratio of NiO to Al2O3 is 1:(1-2), the concentration of the polyvinyl alcohol aqueous solution is 4wt%, wherein the amount of polyvinyl alcohol used is 1.2-1.6wt% of the total mass of NiO and Al2O3.

5. The method for preparing a radiation cooling coating with anti-fouling properties according to claim 1, characterized in that: The following steps are involved: Weigh acrylic resin, TiO2, NiAl2O4, filler, thickener, defoamer, film-forming aid, crosslinking agent and dispersant according to the weight parts of claim 1, then add the components into water and stir to mix evenly to obtain the product.

Citation Information

Cited By

  • Radiation refrigeration coating as well as preparation method and application thereof

    CN120484594A